PELATIHAN INSTALASI CCTV PADA DESA BANDUNGREJOSARI SEBAGAI UPAYA MITIGASI RISIKO BANJIR DAN KEJAHATAN - Chandrasena Setiadi; Isa Mahfudi; Mila Kusumawardani; Hadiwiyatno Hadiwiyatno; Yuri Ariyanto; Retno Damayanti (P3M Politeknik Negeri Malang, 2025)
Bandungrejosari Village RT.05/RW.09, located in Sukun District, Malang City, is vulnerable to flooding due to its proximity to a river and has also faced increasing motorcycle theft. These conditions have raised community concerns and emphasized the need for preventive measures through technology. This program introduced the installation of Closed Circuit Television (CCTV) to support flood mitigation and strengthen neighborhood security, while also providing technical training and awareness on technology-based monitoring systems. The implementation followed a participatory and educational approach, involving stages of preparation, planning, training, installation, and evaluation. Residents actively participated in site surveys, practical device installation, and system simulations, ensuring community ownership of the initiative. Evaluation was conducted through direct observation and questionnaires distributed to 30 respondents. The results indicate that CCTV installation at strategic points effectively assisted in monitoring river conditions and areas prone to crime. Most residents expressed satisfaction, felt supported, and showed willingness to maintain the system. Overall, the program not only improved community preparedness and security but also enhanced collective awareness and participation in sustaining technological solutions for local challenges.